Journal of Thermal Science - Zhu, Junqiang; Zhang, Na.; Chen, Haisheng; SpringerLink (Online service) (Heidelberg : Science Press : Imprint: Science Press, co-published with Springer.)
Founded in 1992, JOURNAL OF THERMAL SCIENCE, an international multi-disciplinary journal of energy and power sciences in English language sponsored by the Institute of Engineering Thermophysics, Chinese Academy of Sciences, publishes high quality papers of original work on experimental, numerical and theoretical investigations from contributors throughout the world. The scope of the Journal covers the following aspects: engineering thermodynamics, fluid mechanics, aerothermodynamics of internal flows, heat and mass transfer, combustion and reaction; sustainability of energy systems; energy conservation and storage; energy efficiency and climate change mitigation; renewable energy; nuclear energy; building, urban and distributed energy systems; cooling and refrigeration, heat pump; transport energy and emissions; operation, diagnostics and control of energy systems; energy policy and management. Review papers and scholarly research articles of high scientific/technical quality related to the development, advancement, and improved understanding of energy, power and environment sciences are sought. The Journal also incorporates technical notes, short communications, and discussions on previous published papers.
Keywords: Continuum physics; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluid mechanics; Classical and Continuum Physics; Engineering Fluid Dynamics; Engineering Thermodynamics, Heat and Mass Transfer